Marketplace-Driven Internationalization and MSME Product Development : (A Case Study of PT Bungas Food Nusantara) - Rahajeng Cahyaning Putri Cipto; Sudarmiatin Sudarmiatin; Heri Pratikto (International Journal of Economics and Management Sciences, 2026)
This study aims to analyze the role of marketplace in encouraging digital internationalization and product development at PT Bungas Food Nusantara. The research uses a qualitative approach with a case study method. Data was obtained through in-depth interviews with company management, observation of activities on the marketplace platform, and supporting documentation. The results of the study show that marketplaces function not only as digital distribution channels, but also as strategic infrastructure that allows companies to reach international markets without conventional export mechanisms. Internationalization occurs gradually through increased demand from overseas consumers facilitated by the platform's algorithmic system and global visibility. In addition, the marketplace's reviews, ratings, and analytics features are used as the basis for product development, including packaging adjustments, variant innovation, and data-driven promotional strategies. These findings show that marketplaces play a role as a catalyst for internationalization as well as a driver of product innovation in the context of the digital economy.